Macrofoundations : exploring the situated nature of activity - W.J Steele, Christopher; R. Hannigan, Timothy; L Glaser, Vern; Toubiana, Madeline; Gehman, Joel (Emerald Publishing Limited, 2020)
This volume of Research in the Sociology of Organizations explores the institutional macro foundations of action, providing an array of insights into the constitutive and contextualizing powers of institutions, and an agenda for further exploration of these themes. The recent increase in attention to the micro foundations of institutions has been fruitful, but risks obscuring institutions' constitutive and contextualizing powers. This volume addresses this risk by focusing attention on how institutions shape the workings of the social and material world, our fundamental experiences, and the real-time unfolding of activity. It examines these institutional macro foundations, and provides rich accounts of the ways in which macro foundations shape and are shaped by micro-dynamics, in a co-constitutive interplay. This volume will be essential reading for management researchers, students, and all those interested in organization and organizational life.
Prelims -- Section 1. Introduction -- Macrofoundations: Exploring the Institutionally Situated Nature of Activity -- Section 2. Definitions and Pontifications -- Chapter 1: Integrating and Complicating the Micro and Macro "foundations" of Institutions: Toward a More Optometric Institutionalism and an Institutionalist Optometry -- Section 3. Macrofounding the Local -- Chapter 2: Institutional Power and Organizational Space: How Space Constrains Micro-level Action in the Emergency Department -- Chapter 3: In the Land of Sand and Oil: How the Macrofoundations of a Tribal Society Shape the Implementation of PublicPrivate Partnerships -- Chapter 4: Punishment and Institutions: A Macrofoundations Perspective -- Section 4. Localizing the Macrofoundational -- Chapter 5: Fighting "Factory Fiction": The Evolution of a Marginalized Institutional Logic in UK Trade Book Publishing -- Chapter 6: New Structuralism and Field Emergence: The Co-constitution of Meanings and Actors in the Early Moments of SOCIAL Impact Investing -- Chapter 7: How Cities Think: Thought Style, Thought Collective, and the Impact of Strategy -- Section 5. Reflections and Future Directions -- Chapter 8: Rediscovering the Macrofoundations of Institutions: Reflections on the Language of Institutional Theory -- Chapter 9: Rediscovering the Power of Institutions: The MacroFoundations of Institutional Analysis -- Chapter 10: Revisiting the Foundations of Institutional Analysis: A Phenomenological Perspective -- Chapter 11: Turtles All the Way Down And Up: Macro-Institutions -- Index.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Organizational sociology; Social Science -- Sociology -- General; Organizational theory & behaviour